Financial development and real exchange rate misalignments effects on environmental pollution - Xiao, Lin; Ahmad, Muneeb; Waseem, Liaqat Ali; Ahmad, Muhammad Munir; Khan, Ashfak Ahmad (Frontiers in Environmental Science, 2022)
The research examined the influence of the fundamental exchange rate misalignment and Least Developed Countries (LDCs) in Asia and Africa’s financial development on CO2 emissions in Asian countries using panel data from 1970 to 2021. The methodology consists of ARDL bound testing and PMG/ARDL estimators with dynamic OLS estimators. The results reveal that the long-run real exchange rates for least developed countries (LDCs) are expected to rise in CO2 emissions in Asian and African countries with improved trade and net foreign asset positions. The relative productivity and trade openness also increase the exchange rate, which also plays a vital role in the growth of CO2 emissions. Except for Egypt, all least developed countries (LDCs) currencies are overpriced throughout the research period at the same time; it would be harmed by increased openness, foreign direct investment inflows, and currency misalignment. Overvaluation harms Bahrain’s economic growth. In comparison, undervaluation helps Egypt that currency misalignment does not affect financial growth in any LDCs over the long run. In the short-run, more real investment, net foreign assets, and official assistance inflows would enhance financial growth in Qatar, Bahrain, Singapore, and South Korea. In contrast, trade openness would slow it down in Egypt and Kuwait. The study suggested that the poor economic performance is due to RER misalignment, which occurs when exchange rate policies are improper and causes a rise in CO2 emissions in many developing countries.